Editorial - Padaria, R N (Indian Journal of Extension Education, 2020)
Information is the fifth need of man after air, water, food and shelter. It became more evident in the scenario in the era of climate change is pretending serious challenges to the agriculture sector in order to ensure nutritional and food security for growing population, changing consumer appreciations, decreasing land sizes, abiotic stresses, lowerseed replacement ratio, demand for more food and processed products to ensure nutritional security poses and so on. Few of the challenges are being taken care through various technological solutions like water management, home science technologies, nutria garden establishment, conduction of front line demonstrations and their systematic analysisin agricultural growth, FDI in agriculture, stress on dairying and associate animal husbandry practices to support the crop production and so on. The present issue of Indian Journal of Extension Education is an amalgam of the extension issues and the solutions offered through its vast network of technology transfer and the topics of academic interest like organizational climate and academic performance of stakeholders in institutes of excellence. It is crucial for extension organizations to impart management skills to farmers and youth to effectively manage the resources including human resources, enterprises and technologies.I extend my sincere thanks to all the authors to present the outcome of extension endeavors with empirical evidence and suitable research design and to all the expert members in the editorial board. Special thanks are extended to the President, ISEE; Dr. US Gautam for providing insightful thoughts and guidance in bringing out this issue.Dr. Bhanu Mishra, Dr. M. S. Nain, Dr. Shantnu Dubey, Dr. S.R.K. Singh, Dr. Alok Kumar, Dr. L. K. Tyagi and team deserve special thanks for making committed efforts in compiling and thorough editing of the papers.(Rabindra Nath Padaria)